Short pulse generation in active Q-switched Yb-doped all fiber laser and its amplification. (January 2019) - Chakravarty, Usha; Gurram, Srikanth; Kuruvilla, Antony; Upadhyaya, B.N.; Bindra, K.S.
Highlights: Sub-cavity round-trip time pulses in all fiber YDF laser with AOM were generated. Generation of pulses were studied in four experimental setups. Pulses appear to generate after the ON time of AOM. Pulses of 50–55 ns were achieved in cavity with round-trip time of ∼130 ns. Pulses with 55 ns duration were amplified ∼19 W average power in two stages. Abstract: Generation of stable sub-cavity round-trip time pulses have been achieved in all-fiber Ytterbium-doped Q-switched fiber laser by controlling the modulation window ON-time of acousto-optic modulator (AOM). Short pulses (anomalous pulses) of duration in the range of 50–55 ns have been achieved in experimental configurations with the cavity round-trip time of ∼130 ns, when modulation window "ON-time" of AOM was equal to or shorter than the pulse build-up time of the normal Q-switched pulses. In the case of normal AO Q-switching, pulses of duration more than 1.3 µs with an average power of 30 mW and pulse energy of 0.38 µJ at 80 kHz of repetition rate were obtained at 2 W of pump power. At the same value of the pump power, the anomalous pulses of ∼55 ns with an average power of 12 mW were generated, which are ∼24 times shorter than pulses obtained with conventional Q-switching process (normal pulses). The peak power of the anomalous pulses are higher than the normal pulses by the factor of eight at the same value of the pump power. The anomalous pulses from the AO Q-switched oscillator with 55 ns pulse duration have been amplified in single mode Ytterbium doped all fiber amplifier in two stages. Amplified average output power of ∼19 W was achieved with the output pulse energy and peak power of 240 µJ and 4.4 kW respectively in all fiber configuration.